2019
DOI: 10.1155/2019/9436047
|View full text |Cite
|
Sign up to set email alerts
|

MCOLN1 Promotes Proliferation and Predicts Poor Survival of Patients with Pancreatic Ductal Adenocarcinoma

Abstract: Background. MCOLN1 (mucolipin subfamily, member 1) was first identified as an autophagic regulator, which was essential for efficient fusion of both autophagosomes and late endosomes with lysosomes. This study is aimed at investigating the role of MCOLN1 in the development of pancreatic ductal adenocarcinoma (PDAC). Methods. Immunohistochemistry (IHC) assay was conducted to evaluate the expression level of MCOLN1 in 82 human PDAC tumor tissues. Overall survival (OS) and recurrence-free survival (RFS) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…In non-small-cell lung cancer, increased TRPML1 expression is observed at high tumor stages and is positively correlated with tumor proliferation, migration, and invasion [ 26 ]. Consistent with this finding, TRPML1 expression is also increased in pancreatic ductal adenocarcinoma (PDAC) patients and negatively correlates with patient overall survival and recurrence-free survival [ 27 ]. Since cancer cells aggressively augment protein synthesis machineries to stimulate cell proliferation, cancer cells experience elevated proteotoxic stress due to increased occurrences of translational infidelity and susceptibility to protein misfolding in the endoplasmic reticulum, potentially triggering cell death [ 28 , 29 ].…”
Section: Main Documentmentioning
confidence: 76%
“…In non-small-cell lung cancer, increased TRPML1 expression is observed at high tumor stages and is positively correlated with tumor proliferation, migration, and invasion [ 26 ]. Consistent with this finding, TRPML1 expression is also increased in pancreatic ductal adenocarcinoma (PDAC) patients and negatively correlates with patient overall survival and recurrence-free survival [ 27 ]. Since cancer cells aggressively augment protein synthesis machineries to stimulate cell proliferation, cancer cells experience elevated proteotoxic stress due to increased occurrences of translational infidelity and susceptibility to protein misfolding in the endoplasmic reticulum, potentially triggering cell death [ 28 , 29 ].…”
Section: Main Documentmentioning
confidence: 76%
“…Yin et al [ 122 ] found that the expression of TRPML1 increases along with the progression of human nonsmall-cell lung cancer (NSCLC). Similarly, by evaluating the expression levels of TRPML1 in tumor tissues from 82 pancreatic ductal adenocarcinoma (PDAC) patients, Hu et al found that a higher TRPML1 expression level is associated with the poor clinical characteristics of these PDAC patients [ 123 ]. Compared with patients with low TRPML1 expression, patients with high TRPML1 expression have significantly lower overall survival.…”
Section: The Lysosomal Ca 2+ Channel Trpmls In mentioning
confidence: 99%
“…Compared with patients with low TRPML1 expression, patients with high TRPML1 expression have significantly lower overall survival. A role of TRPML1 in PDAC progression is further confirmed by using a cell model showing that the proliferation of PDAC cells is dramatically blocked by TRPML1 depletion, and by using a mouse model showing that TRPML1 is required for the formation and growth of PDAC tumors [ 123 ]. Collectively, these studies suggest that TRPML1 is often upregulated in cancer cells to promote tumorigenesis.…”
Section: The Lysosomal Ca 2+ Channel Trpmls In mentioning
confidence: 99%
“…While insufficient endolysosomal function is associated with inborn errors of metabolism, lysosomal storage, and degenerative diseases, increased biogenesis of these organelles is a recurring theme in cancers (Davidson and Vander Heiden, 2017). Several studies have described roles for the endolysosomal cation channel, TRPML1, in different malignancies (Hu et al, 2019;Kasitinon et al, 2019;Xu et al, 2019;Yin et al, 2019). A common theme in these studies is that TRPML1 is necessary for malignancy promoting signaling cascades involving RAS-MAPK and mTORC1.…”
Section: Introductionmentioning
confidence: 99%
“…Since inhibition of TRPML1 arrests proliferation or induces cell death in cancers with elevated expression of the CLEAR network genes (Hu et al, 2019;Jung and Venkatachalam, 2019;, tumors with hyperactivated TFEB/TFE3/MITF signaling are addicted to TRPML1.…”
Section: Introductionmentioning
confidence: 99%